Roosevelt Elementary School - Kjysten Drew:::Creator::::::::::::
Former West End School (Roosevelt Elementary School since 1925). John Steinbeck attended here from grades 3 - 8 (1910 - 1915?) and Olive Steinbeck, John's mother, attended high school here. In East of Eden, Cal and Aron attend school here. Original is slide.